Paduan Suara Sebagai Media Sosialisasi Program Keluarga Berencana Daerah Istimewa Yogyakarta Tahun 2011‐2015 - Suryati Suryati (PROMUSIKA, 2015)
The annual Family Planning (KB) March choir competition as a socialization media of governmental family planning program is held in cooperation between the Yogyakarta “Pamungkas” 072 Military Resort Command (known as the Korem 072/ Pamungkas) with the Family Planning Coordinating Board (known as the BKKBN) of Yogykarta Special Region office, to win the bullet‐shaped rotating trophy provided by the Korem 072/ Pamungkas. The purpose of the competition is to socialize  the “Mars KB” song in all levels of the KB program coverage territories, as well as their working patners, in order to influence the living style of families Yogyakarta through the song theme that covers the  governmental programs of population, family planning, and family welfare empowerment. Although the choir competition has been carried out since 2008, this study is focused on the last 5 years events, from 2011 to 2015. This study untilized a qualitative research method that based on data collection from field studies and literature sources. The three research provlems discussed in thi study are: (1) Why chorus has been used as a medium for family planning programs dissemination; (2) how is public response to the choral competition as it is seen from the number of participants, their vocal quality, and their creative ability, which annually has increased. (3) What is the impact of these  soscialization efforts toward the living style changes on Yogyakarta families as well as people understanding on the family planning  programs. This study concludes that choir competition is the effectif media for this governmental progams due to the involvement of various social type of family members as seen in the participant list during the last five years. Most families in Yogyakarta are seem to agree that the successful family planning demanding equally active role from both husband and wife.